2022
DOI: 10.1002/jsfa.12333
|View full text |Cite
|
Sign up to set email alerts
|

Influence of biochar‐based urea substituting urea on rice yield, bacterial community and nitrogen cycling in paddy fields

Abstract: BACKGROUND There is an increasing understanding of the importance of biochar‐based fertilizers in agroecosystems. However, no research has evaluated the effects of partial substitution of urea with biochar‐based urea on rice yields and soil microbial communities. We therefore investigated the rice yields, bacterial communities, and gene abundance involved in nitrogen in silty clay and sandy loam soil paddy fields treated with urea (U), total substitution of urea with biochar‐based urea (BSU), partial substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…Incorporating urea fertiliser into aerobic soil prevents N loss due to NH 3 volatilisation (Dominghetti et al 2016). Zhang et al (2022) reported the partial substitution of urea with biochar in panicle initiation has a more substantial yield-increasing effect and lowered the risk of nitrogen pollution in silty clay soils and sandy loam soils in paddy fields.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporating urea fertiliser into aerobic soil prevents N loss due to NH 3 volatilisation (Dominghetti et al 2016). Zhang et al (2022) reported the partial substitution of urea with biochar in panicle initiation has a more substantial yield-increasing effect and lowered the risk of nitrogen pollution in silty clay soils and sandy loam soils in paddy fields.…”
Section: Resultsmentioning
confidence: 99%